The Effect of Pre-Teaching Vocabulary in Teaching Reading Skill to Improve Students’ Reading Comprehension - Pingky Rahayu Putri; Yenni Rozimela (Journal of English Language Teaching, 2023)
Reading is very important and essential for students, as their learning success is highly dependent on their reading comprehension. The phenomenon that is seen today is that many students are very poor at understanding a text or do not know the meaning of words in English, this due to the lack of vocabulary they have. This study aims to see the effect of pre-teaching vocabulary in teaching reading skill to improve students reading comprehension. This study used quasi-experimental research. The tests are used to collect the data (pre-test and post-test). The research consists of two class, experimental and control class. The data shows that the experimental class has increased in value after using the pre-teaching technique. It means that the use of pre-teaching vocabulary in improving students’ reading comprehension is effective. In contrast to the control class, they had difficulty understanding a text when reading due to a lack of vocabulary and not being distracted during the learning process.